Contribution of angiotensinogen M235T and T174M gene variants and haplotypes to preeclampsia and its severity in (North African) Tunisians. (January 2018) - Zitouni, Hedia; Ben Ali Gannoum, Marwa; Raguema, Nozha; Maleh, Wided; Zouari, Ines; Faleh, Raja El; Guibourdenche, Jean; Almawi, Wassim Y; Mahjoub, Touhami
Background: Preeclampsia (PE) is a pregnancy-associated hypertensive disorder and a leading cause of maternal and neonatal morbidity and mortality. While its pathogenesis remains ill defined, several candidate genes for PE have been identified, but results remain inconclusive. We investigated the association of the angiotensinogen ( AGT ) gene variants M235T and T174M with PE, and we analyzed the contribution of both variants to the severity of PE. Methods: This case-control study enrolled 550 Tunisian pregnant women: 272 with PE, of whom 147 presented with mild, and 125 with severe PE, along with 278 unrelated age- and ethnically matched control women. AGT genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism. Results: Significantly higher M235T minor allele frequency (MAF) was associated with increased risk of PE ( p < 0.001). Decreased frequency of heterozygous T174M genotype carriers were found in control women ( p = 0.015), suggesting a protective effect of this genotype (odds ratio (95% confidence interval) = 0.51 (0.29–0.89)). Two-locus haplotype analysis demonstrated MM and TT haplotypes to be negatively and positively associated with PE, respectively. MAF of M253T, but not T174M, was higher in the severe PE group, and carrying M235T or T174M minor allele was associated with increased body mass index ( p < 0.001) among unselected PE women. Conclusions: AGT M235T and T174M variants contribute to an increased risk of developing PE, and for M235T to PE severity.